2014
DOI: 10.1111/jph.12285
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversities of Cymbidium mosaic virus and Odontoglossum ringspot virus Isolates Based on the Coat Protein Genes from Orchids in Guangdong Province, China

Abstract: Orchids are some of the most important ornamental flowers. Cymbidium mosaic virus (CymMV) and Odontoglossum ringspot virus (ORSV) are the most prevalent and economically important viruses affecting orchids in China. In this study, 20 CymMV and 28 ORSV isolates were selected for genetic diversity analysis. The CymMV isolates shared 84.6-100% and 89.5-100% identities of coat protein (CP) at the nucleotide (nt) and amino acid (aa) levels, respectively. The identities of ORSV isolates were 96.4-100% (nt) and 92.5-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 8 publications
0
3
0
1
Order By: Relevance
“…(Lawson 1990), Brazil (Freitas et al 1999), India (Sherpa et al 2006), Singapura (Wong et al 1994). Taiwan (Chang 2008), Korea (Chang et al 1991), Cina (Rao et al 2015), dan Taiwan (Zheng et al 2008). Berdasarkan hal tersebut, cara lain yang efektif untuk melindungi dan mempertahankan status kesehatan anggrek asli di Indonesia ialah dengan membatasi dan mengontrol impor anggrek dari negara lain.…”
Section: Pembahasanunclassified
“…(Lawson 1990), Brazil (Freitas et al 1999), India (Sherpa et al 2006), Singapura (Wong et al 1994). Taiwan (Chang 2008), Korea (Chang et al 1991), Cina (Rao et al 2015), dan Taiwan (Zheng et al 2008). Berdasarkan hal tersebut, cara lain yang efektif untuk melindungi dan mempertahankan status kesehatan anggrek asli di Indonesia ialah dengan membatasi dan mengontrol impor anggrek dari negara lain.…”
Section: Pembahasanunclassified
“…For cDNA synthesis and amplification of the CP gene, we used a PrimeScript II High Fidelity One Step RT-PCR kit (Takara, Dalian, China). The previously reported primers described by Rao et al (2015) were used to amplify CP gene. The RT-PCR products were separated by electrophoresis in agarose gels and purified using the QIAquick Gel Extraction Kit (Qiagen, Beiing, China).…”
Section: Methodsmentioning
confidence: 99%
“…Earlier studies reported the genetic variability of ORSV isolates from Korea (Ajjikuttira et al, 2002; Yoon et al, 2011) and China (Rao et al, 2015). These showed high sequence conservation in CP gene.…”
mentioning
confidence: 99%
“…The viral RNA was extracted by TaKaRa MiniBEST Plant RNA Extraction Kit (TaKaRa). One step RT-PCR was performed using a kit (Tiangen) according to the manufacturer's instructions, and the primers reported by Rao et al (2015), which amplified a 500 and 600 bp long region of the CP gene of the two viruses, respectively. ORSV was detected in twenty-four (96%) C. goeringii samples by RT-PCR.…”
mentioning
confidence: 99%